Da'wah and Religious Harmony: Grounding Harmony in Diversity - Haryanto, Rudi; Karni, Awis; Ashadi, Andri (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This study examines da'wah and religious harmony which are important issues in the social context in Bengkalis Regency. Although the majority of the population embraces Islam, there are Christians, Buddhists, and others who coexist. This research aims to identify the role of da'wah in maintaining religious harmony and explore the factors that affect the success of da'wah in creating harmony in the midst of diversity. The research method used is a qualitative approach with in-depth interview techniques with religious leaders, community leaders, and parties involved in da'wah activities in Bengkalis Regency. The findings show that da'wah based on religious moderation has a significant role in reducing social tensions and building awareness of the importance of harmony between religious communities. Da'wah that is carried out with an inclusive and dialogical approach, and involves all elements of society, has proven to be effective in creating an atmosphere of mutual understanding and respect for differences This study concludes that da'wah must be strengthened with a more contextual approach and based on national values to maintain harmony in a diverse society.